Regulatory framework in Pakistan: situation analysis of medicine quality and future recommendations - Huma Rasheed; Ludwig Hoellein; Khalid Saeed Bukhari; Ulrike Holzgrabe (Taylor & Francis Group, 2019)
Background Quality issues in pharmaceuticals are identified as a huge global and public health problem, especially with reference to low- and middle-income countries like Pakistan. The 2011 "Fake Drug Crisis" acted as a driving force to reform the regulatory structures of the country and for establishing the autonomous "Drug Regulatory Authority of Pakistan". Despite the fact that Pakistan possesses a huge pharmaceutical industry, there is a severe dearth of published literature and scientific evidence for the country regarding medicine quality and the prevalence of counterfeit and low-quality products, respectively. Aims and objectives This narrative review covers relevant features of the regulatory framework for pharmaceuticals in Pakistan, its national pharmaceutical industry, as well as a compilation and analysis of published literature for documentation of the country's situation regarding the overall quality of medicines. Methods Available data including scientific publications on the quality of pharmaceuticals in peer reviewed journals, research reports, notifications, and alerts issued by the World Health Organization and other agencies were accessed and compiled. Post graduate dissertations were used to represent unpublished research data and drug safety alerts issued from the local Pakistan authority were analysed to assess the type and number of quality failures reported for pharmaceuticals. Results It could be clearly shown that there is negligible scientific data available on the issue of medicine quality in Pakistan. The anticipated number of 40-50% of poor-quality drugs in Pakistan cannot be defended by data available from the literature. Accessible technologies and strategies used in recent years at global level, especially in developing countries, were also reviewed and recommendations are devised for Pakistan to combat the fight against poor-quality medicines. Conclusion The case reports, investigations, and general data listed for Pakistan suggest the need of strengthening regulatory systems for premises and GMP inspections, analytical laboratories, as well as an overall capacity building in the field of unravelling and controlling substandard and falsified medicines. It is proposed that well-planned and properly funded studies need to be carried out for collecting critical statistics regarding the prevalence of substandard and falsified medicines in Pakistan.